Development of a Computer-Based Laboratory Equipment Record System at SMA Negeri 1 Mutiara, Pidei Regency - Nurbayani (Journal Dekstop Application (JDA), 2024)
The advancement of information technology has significantly impacted various sectors, including education. One of the critical areas in education is the management of laboratory equipment, which traditionally relies on manual systems. This study focuses on the development of a computer-based information system for managing laboratory equipment at SMA Negeri 1 Mutiara, Pidei Regency. The existing manual system was found to be inefficient, leading to frequent errors, delays in maintenance, and difficulties in tracking equipment. The primary goal of this research is to design and implement a system that can automate the recording, categorization, and reporting of laboratory equipment, thus improving the efficiency and accuracy of the process. By utilizing tools such as Microsoft Access and Visual Basic, the proposed system integrates data management processes, providing a more streamlined and error-free system for equipment management. The research follows a structured approach, starting with system analysis, followed by database design, system development, testing, and implementation. The system is designed to be user-friendly, allowing school staff to manage equipment data efficiently, generate timely reports, and ensure proper maintenance. The implementation of this system is expected to reduce errors, speed up data entry, and facilitate better decision-making regarding equipment procurement and maintenance. This study aims to demonstrate the potential of computer-based systems in improving the management of educational resources, ultimately contributing to a more efficient and effective learning environment.